Endoscopic Paramaxillary Approach: A Novel Approach to the Middle Cranial Fossa, Hypoglossal Canal, and Jugular Foramen - Pulido, Ricardo W.; Abuzeid, Waleed M.; Reeve, Nathaniel; Montoure, Andrew; Bly, Randall; Moe, Kris (Journal of Neurological Surgery Part B: Skull Base, 2025)
Provide analytical data of the endoscopic paramaxillary approach, a transoral pathway through the infratemporal fossa, in accessing the middle cranial fossa, hypoglossal canal, and jugular foramen.A combination of five fresh-frozen and vessel-injected cadaver specimens underwent dissection using the endoscopic paramaxillary approach. A step-by-step dissection was completed. An endoscopic transpterygoid approach was performed for endoscopic comparison. Computer modeling and pathway analysis were performed to acquire several quantitative metrics of clinical importance. A far-lateral approach was performed to demonstrate standard of care intradural exposure.WWAMI Institute for Simulation in Healthcare – Harborview Medical Center.Otolaryngology resident and attendings, neurosurgery skull base fellow, and rhinology/skull base fellow.Access the middle cranial fossa, hypoglossal canal, and jugular foramen with preservation of neurovascular structures. Distance, angle of approach, and exposure were quantified using computer modeling and data analysis.Surgical access to the middle cranial fossa, extradural hypoglossal canal, and extradural jugular foramen contents was achieved using the endoscopic paramaxillary approach and endoscopic transpterygoid approach in all cases. Both endoscopic approaches were unable to access the intradural component of the hypoglossal nerve and jugular foramen contents. Distance to the surgical targets was more direct and reduced by 1.5- to 2-fold using the endoscopic paramaxillary approach.The endoscopic paramaxillary approach provides adequate access to the extradural hypoglossal canal, jugular foramen, and middle cranial fossa with preservation of critical neurovascular structures that is more direct and shorter compared with the endoscopic transpterygoid approach.
Keywords: middle cranial fossa; skull base; transpterygoid approach; hypoglossal canal; jugular foramen; endoscopic; paramaxillary; transoral